Candida endocarditis: systematic literature review from 1997 to 2014 and analysis of 29 cases from the Italian Study of Endocarditis. Issue 9 (2nd September 2017) - Giuliano, Simone; Guastalegname, Maurizio; Russo, Alessandro; Falcone, Marco; Ravasio, Veronica; Rizzi, Marco; Bassetti, Matteo; Viale, Pierluigi; Pasticci, Maria Bruna; Durante-Mangoni, Emanuele; Venditti, Mario
ABSTRACT: Introduction : Candida Endocarditis (CE) is a deadly disease. It is of paramount importance to assess risk factors for acquisition of both Candida native (NVE) and prosthetic (PVE) valve endocarditis and relate clinical features and treatment strategies with the outcome of the disease. Areas covered : We searched the literature using the Pubmed database. Cases of CE from the Italian Study on Endocarditis (SEI) were also included. Overall, 140 cases of CE were analyzed. Patients with a history of abdominal surgery and antibiotic exposure had higher probability of developing NVE than PVE. In the PVE group, time to onset of CE was significantly lower for biological prosthesis compared to mechanical prosthesis. In the whole population, greater age and longer time to diagnosis were associated with increased likelihood of death. Patients with effective anti-biofilm treatment, patients who underwent cardiac surgery and patients who were administered chronic suppressive antifungal treatment showed increased survival. For PVE, moderate active anti-biofilm and highly active anti-biofilm treatment were associated with lower mortality. Expert commentary : Both NVE and PVE could be considered biofilm-related diseases, pathogenetically characterized by Candida intestinal translocation and initial transient candidemia. Cardiac surgery, EAB treatment and chronic suppressive therapy might be crucial in increasing patient survival.